The Effect of Work Motivation, Compensation, and Work Discipline on Employee Performance at PT Darma Panca Samudera - Bagas Estiawan Soedarsono; Maulidyah Amalina Rizqi (Universitas Muhammadiyah Gresik, 2023)
This study aims to determine the effect of motivation, compensation, and work discipline on employee performance at PT. Dharma Five Ocean. This study uses a quantitative approach. The sampling technique used a saturated sample with the number of samples obtained as many as 85 respondents . The population used in this study were all employees of PT. Dharma Panca Samudera. The data analysis technique used in this research is the multiple linear method. The results showed that the regression equation was obtained Y=8.715+0.428X 1 +0.541X 2 +0.461X 3 . The results of the analysis show that motivation has a significant positive effect on employee performance with a significant value of 0.05 or 0.026 <0.05. Compensation has a significant positive effect on employee performance with a significant value of 0.05 or 0.000 <0.05. Work discipline has a significant positive effect on employee performance with a significant value of 0.05 or 0.004 <0.05. It is recommended that to improve employee performance, management is expected to need to increase employee morale in carrying out tasks that are the responsibility of employees so as to improve work discipline and also improve employee performance. The management should provide increased benefits and incentives to employees so that they can improve the performance of employees in the company.